Niektóre uwarunkowania zmian strukturalnych w rolnictwie polskim - Trzęsowski, Michał (Wydział Prawa i Administracji UAM, 1985)
The program of structural changes in our farming, initiated in the past and oriented at direct forms of socialising the land, has not brought any satisfactory results. The course aiming at national self-sufficiency in food, in the conditions of limited supplies of the means of production, forces us to seek new solutions, ones which would to a greater extent take into account the specific nature of our farming. The great differences in the production and economic results of the various agricultural sectors enables us to see the perfecting of agricultural structural as one of the instruments of raising the effectiveness of management. Yet the realisation of structural plans in agriculture would require certain adjustment changes in the whole complex of the food industry.
Some of the Conditions of Structural Changes in Polish Agriculture